2020
DOI: 10.1007/s11325-020-02202-1
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in sleep quality during COVID-19 outbreak

Abstract: Purpose The COVID-19 outbreak witnessed in the first months of 2020 has led to unprecedented changes in society's lifestyles. In the current study, we aimed to investigate the effect of this unexpected context on sleep. Methods During the COVID-19 outbreak, we performed an online survey with individuals formerly recruited for validation of the Spanish version of the sleep questionnaire Satisfaction, Alertness, Timing, Efficiency, and Duration (SATED). In the current survey, we asked the participants to complet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 21 publications
9
47
2
2
Order By: Relevance
“…Both SQ and AQ are significantly associated with several factors. Like other studies, we found poor SQ and AQ in young adults [ 11 ], females [ 10 , 11 , 18 , 19 ], higher-education individuals [ 19 , 26 ], and healthcare workers (medical doctors (MDs) and nurses) [ 7 , 14 , 24 , 31 , 32 , 33 ]; however, civil status was not an influencing factor, except for AQ, and the oldest group had higher SQ and AQ levels. The differences in married people are in line with the data concerning the number of people living together; SQ was better for two persons while AQ was better for 1–4 persons.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Both SQ and AQ are significantly associated with several factors. Like other studies, we found poor SQ and AQ in young adults [ 11 ], females [ 10 , 11 , 18 , 19 ], higher-education individuals [ 19 , 26 ], and healthcare workers (medical doctors (MDs) and nurses) [ 7 , 14 , 24 , 31 , 32 , 33 ]; however, civil status was not an influencing factor, except for AQ, and the oldest group had higher SQ and AQ levels. The differences in married people are in line with the data concerning the number of people living together; SQ was better for two persons while AQ was better for 1–4 persons.…”
Section: Discussionsupporting
confidence: 78%
“…The more affected groups were healthcare workers, mostly those working in frontline services [ 7 , 14 , 24 , 31 , 32 , 33 ], young people [ 11 ], older age [ 7 ], females [ 10 , 11 , 18 , 19 ], males performing highly demanding jobs [ 34 ], people suffering from death in the family [ 20 ], or those living in places with high COVID-19 prevalence [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings regarding SQ are in line with those of others carried out in the context of the pandemic, indicating that con nement is associated with worse SQ (López-Moreno et al 2020;Barrea et al 2020). It is likely that forced con nement results in increased levels of stress/anxiety, as well inability to maintain a physically active lifestyle, which in turn are associates with poorer SQ (Barrea et al 2020;Targa et al 2020;Martínez-de-Quel et al 2021). The fact that women more often experienced poorer SQ is probably explained by the fact that women are more susceptible to suffer greater psychological burden than men under stressful of demanding situations (Sal et al 2020).…”
Section: Sleep Quality (Sq) Among Women and Mensupporting
confidence: 89%
“…An array of recent studies have shown that the COVID-19 pandemic has a detrimental impact on sleep quality, with low sleep quality leading to higher daily dysfunctions ( Cellini et al, 2020 ; Fu et al, 2020 ; Salehinejad et al, 2020 ; Targa et al, 2020 ). In general, the changes in social and work-related schedules as a result of COVID-19-related restrictions lead to alterations in sleep patterns and individuals’ circadian rhythms ( Targa et al, 2020 ), however, the effects of these changes in athletes specifically is still unknown. The cancelation or postponement of competitions, for instance the Olympic Games in Tokyo ( Olympic Games, 2020 ), may also impair professional athletes’ sleep quality due to the inherent uncertainty and disruption of medium- to long-term goals.…”
Section: Slow-paced Breathingmentioning
confidence: 99%